INTEREST IN INVESTING IN MUTUAL FUNDS USING FINTECH APPLICATIONS: DETERMINANTS AND IMPACT ON MUTUAL FUND PURCHASE DECISIONS - Rivan Adji Wibowo; Mas Ning Zahroh (Asosiasi Dosen Muda Indonesia, 2024)
The aim of this research was to analyze interest in investing in mutual funds using an applicationfintech: determinants and their impact on mutual fund purchasing decisions as well as to test the influence of motivation and knowledge on interest in investing in mutual funds and their impact on mutual fund purchasing decisions as well as finding out the most dominant variables. The population in this study were respondents who used the applicationfintech mutual funds. Samples are determined by techniquePurposive Sampling, with 130 respondents. The data collection technique used was a questionnaire. The analysis techniques used in this research are instrument testing (validity test and reliability test), classical assumption test, descriptive statistical analysis, factor analysis, hypothesis testing and coefficient of determination using the SPSS programfor windows 23.0. The research results show that there is a simultaneous or partial influence of motivation and knowledge on interest in investing in mutual funds, there is a simultaneous or partial influence of motivation and knowledge on mutual fund purchasing decisions, and there is an influence of interest in investing in mutual funds on mutual fund purchasing decisions. Based on the partial test results, it can be seen that motivation has the greatest influence on interest in investing in mutual funds and knowledge has the greatest influence on mutual fund purchasing decisions.